Sequence Analysis of the UCP1 Gene in a Severe Obese Population from Southern Italy. (30th May 2011) - Labruna, Giuseppe; Pasanisi, Fabrizio; Fortunato, Giuliana; Nardelli, Carmela; Finelli, Carmine; Farinaro, Eduardo; Contaldo, Franco; Sacchetti, Lucia
Abstract : Brown adipose tissue, where Uncoupling Protein 1 (UCP1) activity uncouples mitochondrial respiration, is an important site of facultative energy expenditure. This tissue may normally function to prevent obesity. Our aim was to investigate by sequence analysis the presence of UCP1 gene variations that may be associated with obesity. We studied 100 severe obese adults (BMI > 40 kg/m 2 ) and 100 normal-weight control subjects (BMI range = 19–24.9 kg/m 2 ). We identified 7 variations in the promoter region, 4 in the intronic region and 4 in the exonic region. Globally, 72% of obese patients bore UCP1 polymorphisms. Among UCP1 variants, g.IVS4−208T>G SNP was associated with obesity (OR: 1.77; 95% CI = 1.26–2.50; P = .001 ). Further, obese patients bearing the g.−451C>T (CT+TT) or the g.940G>A (GA+AA) genotypes showed a higher BMI than not polymorphic obese patients (P = .008 and P = .043, resp.). In conclusion, UCP1 SNPs could represent "thrifty" factors that promote energy storage in prone subjects.